Bacterial Diversity in Pet Rabbits: Implications for Public Health, Zoonotic Risks, and Antimicrobial Resistance - Smaranda Crăciun; Cristiana Ştefania Novac; Nicodim Iosif Fiţ; Cosmina Maria Bouari; Lucia Victoria Bel; George Cosmin Nadăş (Microorganisms)
This study examined epidemiological aspects of rabbit pathologies, identified bacterial strains, and assessed their antimicrobial resistance, emphasizing rabbits as potential reservoirs for zoonotic multidrug resistant (MDR) bacteria and the need for continuous monitoring and antimicrobial stewardship. Samples from rabbits were cultivated and then identified using Vitek® 2 and MALDI-TOF. Antimicrobial susceptibility was assessed by disk diffusion testing. This study analyzed 170 individuals with various pathologies, with males (58.24%) outnumbering females (41.76%). Dental abscesses (35.29%) and respiratory infections (28.24%) were most common. Antibiotic exposure was noted in 47.06% of cases, primarily involving trimethoprim (35.56%). Of the total samples, 91.18% tested positive, revealing 200 isolates from 23 bacterial genera, with Staphylococcus spp. (31%) and Escherichia coli (12%) being most frequently identified as well as species with zoonotic potential, such as Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella pneumoniae, Proteus mirabilis, and Enterococcus faecium. Antimicrobial susceptibility testing showed high efficacy for florfenicol (75%), ciprofloxacin (74.12%), and amikacin (68.65%), while significant resistance was found for kanamycin, neomycin, and trimethoprim. Nearly 49% of strains were MDR, with Gram-positive cocci, Enterobacteriaceae, and non-Enterobacteriaceae showing varying resistance, across 18 MDR genera. In conclusion, pet rabbits are potential reservoirs of zoonotic and MDR bacterial species, posing a risk for their owners.